Determination of Peanut Varieties through Chemical Tests and Electrophoresis of Soluble Seed Proteins - P. S. Rao; M. Bharathi; K. Bayyapu Reddy (Research Highlights in Agricultural Sciences Vol. 4, 2022)
Variety characterization and identification has become invariably significant for purity maintenance during seed production as well as for the varietal protection under plant variety protection. Several aspects of seed trade rely on the ability to characterise and identify plant varieties. Thirty-five peanut (Arachis hypogaea L.) genotypes that are in demand and in the seed production chain were characterised using biochemical tools such as total soluble seed proteins and seed and seedling characteristics for their reaction to NaOH, KOH, GA3, and 2,4-D tests. It was possible to categorise all of the cultivars into different groups such as light brown and dark brown, as well as low, moderate, and high response of coleoptile to respective chemicals. Each of these genotypes has a distinctive banding pattern for soluble seed proteins on SDS-PAGE. There were 11 to 28 bands with various molecular weights. The genotype GG 20 produced the most bands (28) while the genotype GG 12 produced the fewest (11). The qualitative and quantitative differences between the various genotypes were revealed by the seed protein profiles of the genotypes, demonstrating the value of electrophoretic variation in varietal identification.